If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 * 3 + -4Y = 36 Multiply -9 * 3 -27 + -4Y = 36 Solving -27 + -4Y = 36 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + -4Y = 36 + 27 Combine like terms: -27 + 27 = 0 0 + -4Y = 36 + 27 -4Y = 36 + 27 Combine like terms: 36 + 27 = 63 -4Y = 63 Divide each side by '-4'. Y = -15.75 Simplifying Y = -15.75
| (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 | | 16(1/2x)^4 | | 5(2m+1)=4m+12 | | (1-8/9)/((1/5)/9+2/9) | | 5x^2-10=2x^2 | | -5(y+6)=-10 | | 28=x+9 | | -45.00+15.00=15 | | 30=4x | | 3x^2-1=10 | | (1/5)/9+2/9 | | tn=4n-4 | | 32=-2a | | (x+3)/(2) | | 0.84=In(y) | | 30v^6/48v^2 | | x/(91/30)=(1-8/9)/((1/5)/9+2/9) | | .03x+1.8=0.4(x+5).02 | | x/(91/30) | | .4k-.6=1.3k+1.2 | | 3/4x^27x16=0 | | 0.3+1.8=0.4(x+5)2 | | -34=-19+b | | Y=7/10*3-7 | | vf=0+5(4) | | 30x+180=40(x+5)2 | | x^1/2-x^3/2 | | 12=4x^2+8x+2 |